The Effect of A Self-Management Support Program on Dietary Knowledge and Behavior of Type 2 Diabetic Patients with Chronic Kidney Disease Nontan Subdistrict, Nongrua District, Khonkaen Province - Singburan, Phatcharaphorn; Phinyo, Kittiphoom (Journal of The Royal Thai Army Nurses, 2024)
This research was a quasi-experimental research, The two-group pre- and post-experimental study to study the outcomes of a program to support the management of additional knowledge and food management skills for type 2 diabetes indicative of renal impairment. sick Type 2 diabetes mellitus, indicating stage 1-3a of renal impairment, 18 subjects were selected from the experimental group and control group. The experimental group received a 12-week program. The experimental instrument was a self-management support program on dietary knowledge and behavior of type 2 diabetic patients with renal degeneration. Passed the content straightness check from 5 experts. The tools used for data collection were the knowledge questionnaire and the food self-management behavior questionnaire. Confidence was used Kuder Richardson formulas = .8 and .77. Data were analyzed using descriptive statistics, Paired t-test and Independent t-test. The study found that The experimental group after joining the program The mean scores of knowledge and behavior were significantly higher than the control group at the .05 level (p<.05). The suggestion from the research is The program should be adapted to diabetes clinics in sub-district health promotion hospitals and community health centers. Community practice nurses or diabetes care staff in sub-district health promotion hospitals should be trained to have knowledge of food consumption to delay renal impairment by using Canfer’s self-management concept in caring for patients